ANALISIS STRUKTUR JARINGAN DAN PROSES BISNIS DALAM RANTAI PASOK SAYURAN LAHAN PASIR PANTAI - Banun Diyah Probowati; Adi Djoko Guritno; Mochammad Maksum; Dyah Ismoyowati (AGROINTEK, 2021)
The changing paradigm of  the business environment is becoming increasingly dynamic. Supply chain can be a competitive strategy that can improve the ability of business competition to determine critical points in business processes. The supply chain process has a big impact on global business and commerce. Development of an effective supply chain is carried out through the development of network structures in the supply chain, especially for coastal agricultural land vegetables. Vegetables planted in coastal agricultural land have their own uniqueness, which is different from plateau plants because of the nature of the land. Research aimed to analyze the network structure and chain business processes of  vegetable  supply chain in the coastal agricultural land.  Research method used framework process of horticulture supply chain development method that were modified.  The results showed that the supply chain network structure of  vegetable from coastal agricultural land  different from plateau land. There was a network structure of supply chain from farmers / farmer groups to traders in the auction market. Key business  processes in vegetable supply chain of  coastal agricultural land that can support sustainable profits were building trust, coordination, collaboration and policy